2018
DOI: 10.1038/s41598-017-18724-w
|View full text |Cite
|
Sign up to set email alerts
|

Robust fabrication of thin film polyamide-TiO2 nanocomposite membranes with enhanced thermal stability and anti-biofouling propensity

Abstract: The development of nano-enabled composite materials has led to a paradigm shift in the manufacture of high-performance nanocomposite membranes with enhanced permeation, thermo-mechanical, and antibacterial properties. The major challenges to the successful incorporation of nanoparticles (NPs) to polymer films are the severe aggregation of the NPs and the weak compatibility of NPs with polymers. These two phenomena lead to the formation of non-selective voids at the interface of the polymer and NPs, which adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(61 citation statements)
references
References 69 publications
(44 reference statements)
1
60
0
Order By: Relevance
“…TOC and UV 254 are both surrogates' measures of the organic matter in water; however, large aromatic compounds have UV 254 absorbance. Smaller aliphatic compounds have passed through the membrane at a faster rate than larger aliphatic compounds . Thus, TFN membranes do not reject smaller aliphatic compounds as well as the TFC membranes do.…”
Section: Resultsmentioning
confidence: 99%
“…TOC and UV 254 are both surrogates' measures of the organic matter in water; however, large aromatic compounds have UV 254 absorbance. Smaller aliphatic compounds have passed through the membrane at a faster rate than larger aliphatic compounds . Thus, TFN membranes do not reject smaller aliphatic compounds as well as the TFC membranes do.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable Syst. [64] Copyright 2018, Springer Nature. a) Conceptual model of water permeation in the UF versus RO membrane.…”
Section: Membrane Modifications For Antibacterial and Antifouling Appmentioning
confidence: 99%
“…The researchers reported that the newly developed TFN membranes could attain excellent water permeability without compromising membrane selectivity. Other hydrophilic nanofillers that are capable of improving the surface chemistry of RO membrane include silica (SiO 2 ), titanium dioxide (TiO 2 ), graphene oxide (GO) and carbon nanotubes (CNTs) …”
Section: Introductionmentioning
confidence: 99%
“…Other hydrophilic nanofillers that are capable of improving the surface chemistry of RO membrane include silica (SiO 2 ), titanium dioxide (TiO 2 ), graphene oxide (GO) and carbon nanotubes (CNTs). [22][23][24][25] Recently, titanate nanotubes (TNTs) synthesized via the hydrothermal method using TiO 2 nanoparticles as precursors have drawn great attention from researchers. TNT is well known for its strong oxidative power, biological and chemical inertness, and good stability towards chemical corrosion.…”
Section: Introductionmentioning
confidence: 99%